Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content:1. The Impact of Establishment King Abdullah University for Science and Technology  on the Urban Growth in Thuwal Center in Jeddah GovernorateMrs. Aisha Abdulkareem Ataallah Bakhsh2. The role of social media to promote a culture of values and sustainable development  in the Asir regionAdel Mohammed Abumalih3. Cultural dialogue in the Islamic perspective and its role in achieving coexistence among civilizationsMrs. Shaymaa Nasser Hussain Al-Shammari4. The stages of the play’s development from the ancient era to the Umayyad eraCo-Prof. Narjees Abdulghaffar Saeed Bazuhair5. The role of the Barbarossa brothers in extending the Ottoman influence in the central Maghreb (Algeria) (916-953 AH / 1510-1546 AD)Prof. Osama M. Abu Nahel6. Cultural Approach to Literary TranslationDr. Mohamed Sidi Mohamed Sidi Mahmoud7. The Use of Reporting Verbs in Arabic-English Social Science Articles:  A Contrastive Corpus-based AnalysisDr. Jawharah SaeedAlasmari
Keywords: Journal of Humanities & Social Sciences